Size of ischial fibro-ostosis is associated with heterotopic ossification after total hip arthroplasty - Bollmann, Jakob; Bergdolt, Christian; Aldinger, Peter R.; Maier, Michael Wolfgang; Gotterbarm, Tobias; Merle, Christian (International orthopaedics, 2019)
The hypothesis of the present study was that degenerative fibro-ostosis (FO) of the ischial hamstring tendon insertion is a risk factor for heterotopic ossification (HO) following THA.
Gesehen am 03.04.2020
Published: 13 December 2018